ANALYSIS OF WORK MOTIVATION IN AN EFFORT TO INCREASE WORK SPIRIT AT THE EDUCATION AND CULTURE OFFICE OF LIMA PULUH KOTA REGENCY: Analisis Motivasi Kerja dalam Upaya Peningkatan Semangat Kerja di Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota - Wahyudi, Muhammad Fathan Wahyudi; Syamsir (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes work motivation in improving employee spirit at the Department of Education and Culture of Lima Puluh Kota Regency. Low spirit, lack of recognition, limited facilities, and weak discipline were identified as major challenges. This research applied a qualitative descriptive approach. Data collection techniques included observation, interviews with seven informants (consisting of heads of divisions, sub-sections, and staff), and documentation. Data were validated through triangulation. The findings indicate that good working relationships, communicative leadership, and opportunities for training support motivation, while inadequate facilities, unclear reward systems, and weak discipline hinder morale. This study concludes that strengthening recognition, providing adequate facilities, and offering fair career development are crucial to increasing morale and organizational performance. The novelty of this study lies in applying motivation theory to the public sector, especially in the education office, where motivation directly impacts service quality and organizational effectiveness.